The Cambridge companion to Reformed theology - Nimmo, Paul T. 1973-; Fergusson, David 1956-; Cambridge University Press (Cambridge companions to religion, 2016)
"This Companion offers an introduction to Reformed theology, one of the most historically important, ecumenically active, and currently generative traditions of doctrinal enquiry, by way of reflecting upon its origins, its development, and its significance. The first part, Theological Topics, indicates the distinct array of doctrinal concerns which gives coherence over time to the identity of this tradition in all its diversity. The second part, Theological Figures, explores the life and work of a small number of theologians who have not only worked within this tradition, but have constructively shaped and inspired it in vital ways. The final part, Theological Contexts, considers the ways in which the resultant Reformed sensibilities in theology have had a marked impact both upon theological and ecclesiastical landscapes in different places and upon the wider societal landscapes of history. The result is a fascinating and compelling guide to this dynamic and vibrant theological tradition"--